2015
DOI: 10.1289/ehp.1307379
|View full text |Cite
|
Sign up to set email alerts
|

Src-Mediated EGF Receptor Activation Regulates Ozone-Induced Interleukin 8 Expression in Human Bronchial Epithelial Cells

Abstract: Background:Human exposure to ozone (O3) results in pulmonary function decrements and airway inflammation. The mechanisms underlying these adverse effects remain unclear. Epidermal growth factor receptor (EGFR) plays an important role in the pathogenesis of lung inflammation.ObjectiveWe examined the role of EGFR activation in O3-induced expression of the chemokine interleukin 8 (IL-8) in human bronchial epithelial cells (HBEC).MethodsWe detected phosphorylated EGFR using immunoblotting. EGFR dimerization was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Peculiar Src expression and kinase activity have been found in a number of different tumours, including GCs; these changes in expression could upregulate tyrosine phosphorylation of Cav-1 [29, 30] and inhibit the effects of the cell membrane on EGFR endocytosis [31]. Preclinical experiments have demonstrated that Src kinase activity may activate EGFR activity [32]. Cav-1 and p-Cav-1(Y14) were reduced when BGC-823 cells were treated with DT-13; however, the TPT-treated group had the opposite result (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…Peculiar Src expression and kinase activity have been found in a number of different tumours, including GCs; these changes in expression could upregulate tyrosine phosphorylation of Cav-1 [29, 30] and inhibit the effects of the cell membrane on EGFR endocytosis [31]. Preclinical experiments have demonstrated that Src kinase activity may activate EGFR activity [32]. Cav-1 and p-Cav-1(Y14) were reduced when BGC-823 cells were treated with DT-13; however, the TPT-treated group had the opposite result (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…EPA 2014; IARC 2010; McHale et al 2012; Smith 2010; Smith et al 2011; Thomas R et al 2012, 2014), ozone (lung inflammation and injury) (U.S. EPA 2013a, 2014; McCullough et al 2014, 2016; Wu et al 2015), and PAHs (lung cancer) (U.S. EPA 2013b, 2014; Mattes et al 2014)].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for a causal relationship between a specific AOP and adverse effects includes pharmacologic intervention to block identified pathway changes, use of knock-in and knock-out models, or identification of pathway polymorphisms and concomitant amelioration of severity or incidence of the specified adverse outcomes (U.S. EPA 2014; French et al 2015; Hatzimichael and Crook 2013; Kasahara et al 2015; McCullough et al 2014; McHale et al 2012; Smith 2010; Thomas R et al 2014; Wu et al 2015). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of differences in EGFR activation by ligand versus c-Src, the EGFR-STAT3 pathway may be favored when the receptor is activated by the loop phosphorylation mechanism. There are conflicting reports as to whether the Tyr1068 STAT3 docking site is a direct target for c-Src kinase activity, or if c-Src-dependent Tyr845 phosphorylation leads to EGFR activation and the subsequent autophosphorylation at EGFR Tyr1068 (4951). It is also possible that stress-exposed EGFRs are protected from protein tyrosine phosphatases that maintain basal EGFR tyrosine kinase activity (52).…”
Section: The C-src/egfr/stat3 Signaling Axismentioning
confidence: 99%